2017
DOI: 10.1111/jfbc.12366
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of glucosinolates, and the antioxidant activity of Dolsan leaf mustard kimchi extract using HPLC and LC-PDA-MS/MS

Abstract: Leaf mustard (Brassica juncea), the main ingredient of leaf mustard kimchi, has a variety of biologically active secondary metabolites such as glucosinolates (GSLs), flavonoids, and polyphenols. In this study, the changes in GSL content and antioxidant properties during the storage of Dolsan leaf mustard kimchi (DLMK) for 35 days were examined by separation and purification of DLMK extracts using high‐performance liquid chromatography (HPLC) and preparative octadecylsilane‐HPLC. The total GSL content and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Diverse fermentation processes of fermented bamboo shoots and their method of preparation could contribute for the higher antioxidant activity. Oh et al [39] reported that during kimchi manufacturing process the antioxidant components contained in leaf mustard were degraded, similarly in the present study hungrii (73.3 µg/ml) had lower antioxidant activity than brassica/mustard leaves (65.7 µg/ml).…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…Diverse fermentation processes of fermented bamboo shoots and their method of preparation could contribute for the higher antioxidant activity. Oh et al [39] reported that during kimchi manufacturing process the antioxidant components contained in leaf mustard were degraded, similarly in the present study hungrii (73.3 µg/ml) had lower antioxidant activity than brassica/mustard leaves (65.7 µg/ml).…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…Park et al, 2017). Glucosinolate content showed a trend of first decreasing and then increasing during the fermentation process (Oh et al, 2017). During the storage of mustard greens, the content of hydroxycinnamic acid showed a trend of increasing first and then decreasing (Harbaum et al, 2008a).…”
Section: Effects Of Food Processing On Nutritional Components and Biomentioning
confidence: 91%
“…The processing method had a great impact on the nutrient composition of mustard. Polyphenol content in Mustard tended to decrease during fermentation (Harbaum, Hubbermann, Zhu, Schwarz et al, 2008a;Oh et al, 2017) along with a corresponding decrease in flavonoids (Harbaum et al, 2008a;Oh et al, 2017;S.Y. Park et al, 2017).…”
Section: Effects Of Food Processing On Nutritional Components and Biomentioning
confidence: 99%
See 2 more Smart Citations